Child anxiety questionnaire. Psychometric characteristics and comparative descriptive analysis - Córdova Chávez, María (2005)
This article is the result of the application of John Gilli´(1980) Child Anxiety Scale (CAS), standardized and adapted by Gomez and Pulido (1992). The sample was formed by 1087,  6 to 8 years- old- children, first from third grade of primary, from five socioeconomic sectors (high, medium high, medium, medium low, low) of Lima. The results show that the CAS presents and adequate coefficient of confiability and fiability. There are significant differences in variables of age and socioeconomic level in the whole scale.